An Overview and Changing Scenario of Post-graduate Medical Education in Nepal: What Is the Way Forward? - Dangal, Ganesh (Journal of Nepal Health Research Council, 2021)
The goal of the Postgraduate (PG) Medical Education Program in any country is to produce high quality professionals with required clinical competency and capability in teaching, research, leadership, communication, collaboration and health advocacy in addition to sound knowledge of the given specialty. Countries like Nepal should adopt the contemporary global trends and implement innovative approaches in medical education utilizing skill labs, information technologies; computer assisted teaching learning, simulation-based learning if practicable and others. The MD/MS/ or National Board curriculum should reflect and be in line with the core principles advocated by the world leaders/institutes of medical education. Additionally, an institution imparting postgraduate program should provide facilities consistent with the overall academic program including exposure in applied basic medical sciences and other related subjects/areas as prescribed by the regulatory bodies like Medical Education Council (MEC), Nepal Medical Council (NMC), academia and the line ministries; in addition to the required number of faculties of related specialties for facilitating teaching/ learning as per the set guidelines along with facilities of ancillary departments related to the concerned subject as per the requirement of the curriculum as well.